ANTISENSE OLIGONUCLEOTIDES TARGETING HEPATIC ANGIOTENSINOGEN DOSE-DEPENDENTLY REDUCE ATHEROSCLEROSIS AND LIVER STEATOSIS IN HYPERCHOLESTEROLEMIC MICE. (June 2022) - Ye, Dien; Wu, Congqing; Cai, Lei; Howatt, Deborah A.; Liang, Ching Ling; Temel, Ryan E.; Mullick, Adam E.; Danser, A.H. Jan; Daugherty, Alan; Lu, Hong S.
Abstract : Objective: Liver-derived angiotensinogen (AGT) is the substrate from which renin and ACE generate angiotensin (Ang) II. Ang II not only increases blood pressure, but also is a major determinant of atherosclerosis in hypercholesteremic mice. Here we investigated the effect of hepatocyte-specific (N-acetylgalactosamine-conjugated) antisense oligonucleotides targeting AGT (GalNAc AGT ASOs) on blood pressure and atherosclerosis in hypercholesterolemic mice. Design and method: Eight-week-old male LDL receptor deficient mice were fed a Western diet for 12 weeks, after receiving vehicle, GalNAc control ASO, or 1, 2.5 or 5 mg/kg of GalNAc AGT ASO on day 1, 3, 5 and 7 in the week prior the start of the diet (n = 6–10/group). Treatment was continued thereafter on a weekly basis. Systolic blood pressure (SBP) was monitored by tail cuff. After 12 weeks, mice were euthanized and plasma was collected. Plasma AGT concentration was measured by ELISA kit, and aortic atherosclerotic lesion area was measured by an en face method. Results: The 3 GalNAc AGT ASO doses decreased plasma AGT from 10.3 ± 0.8 to 1.4 ± 0.1, 0.9 ± 0.1 and 0.7 ± 0.1 g/mL, respectively. These decreases were paralleled by dose-dependent SBP reductions from 114 ± 3 to 96 ± 2, 92 ± 2, and 84 ± 2 mmHg, respectively, and atherosclerotic lesion area reductions from 27.4 ± 0.9 to 15.1 ± 1.4, 10.8 ± 1.2, and 7.7 ± 1.0%, respectively. Yet, the attenuation of liver steatosis (liver triglyceride/weight from 139.7 ± 35.7 to 26.8 ± 4.5, 19.9 ± 1.2 and 36.0 ± 3.6 g/mg, liver total cholesterol/weight from 19.8 ± 1.6 to 8.6 ± 0.9, 6.1 ± 0.6 and 8.2 ± 0.7 g/mg) was identical for each GalNAc AGT ASO dose. GalNAc control ASO did not have effects on plasma AGT, SBP, atherosclerosis lesion area, or liver steatosis vs. vehicle. Conclusions: In hypercholesterolemic mice, inhibition of hepatic AGT reduces systolic blood pressure and atherosclerosis dose-dependently, while liver steatosis was prevented in dose-independent manner.